User Well-Being as a Paramount Challenge in Contemporary Built Environment Design: The Architecture of Psychiatric Hospitals and Its Influence on Treatment Processes and the Health, Safety, and Comfort of Patients and Medical Staff—A Systematic Literature Review and Insights from the New European Bauhaus Initiative - Daria Pawlaczyk-Szymańska; Agnieszka Gębczyńska-Janowicz; Joanna Zdrojewska; Wacław Szarejko (Buildings)
The natural environment, urban systems, and the buildings in which we live, study, work, or undergo treatment affect our mental health. The aim of this literature review was to verify the state of knowledge on the impact of the forms of psychiatric hospital buildings and the architectural solutions used inside these facilities on their comfort and safety of use, more effective forms of therapy, and the health of patients, as well as the comfort and safety of medical staff. This literature review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The scientific databases that were accepted for review were Scopus, Web of Science, and PubMed. During the preliminary analysis, During the initial analysis, 175 potential publications addressing the architecture of psychiatric hospital buildings were obtained. After three-stage verification, 31 English-language publications qualified for the review. The review showed the state and form of the architecture of psychiatric hospitals. The obtained results confirm the significant impact of the buildings and interiors of psychiatric wards and hospitals on the safety, comfort, and well-being of their users, as well as on achieving better therapeutic effects. The literature review not only examined the current state and form of the architecture in psychiatric hospitals but also the architectural solutions increasingly used in these facilities in order to improve the quality of the space, which affects its users.